PKM PELATIHAN PERAKITAN ELEKTRONIKA SEBAGAI BEKAL KETERAMPILAN GENERASI MILENIAL DI KOTA TASIKMALAYA - Risnandar, Muhammad Aris; Sambas, Aceng; Ula, Shofiatul (Universitas Muhammadiyah Tapanuli Selatan, 2019)
The Ar-Ridho PKBM and the Majelis Pemberdayaan Masyarakat (MPM) of the Muhammadiyah Regional Leadership of the city of Tasikmalaya have a large contribution to the community empowerment program in the city of Tasikmalaya. However, the institution has limitations related to training, limited funds, human resources, and other supporting facilities. The problem is related to the lack of Tasikmalaya city people who have skills in the field of technology, so people do not have good skills in dealing with global competition. Therefore, we conduct electronic assembly training activities with a focus on providing electronic assembly skills for the millennial generation. The material presented includes the concept of introducing electronic components, measuring electronics and assembling light sensors on garden lights. With the provision of skills such as this millennial generation is expected to have the basic skills that are used as provisions for entrepreneurship and become productive economically and socially.